Pengaruh Investment Opportunity Set, Total Asset Turn Over, Dan Earning per Share dengan Dividen Tunai (Studi Pada Perusahaan Manufaktur Yang Terdaftar di BEI periode 2009-2013) - Raida Fuadi; Ainul Julia Satini (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2015)
The purpose of this research is to determine the influence of investment opportunity set, total asset turn over, and earning per share on cash dividend at manufacturing company listed in Indonesia Stock Exchange (BEI) during 2009 until 2013. The method used in this research is purposive sampling method. The sample of this research is manufacturing company listed in Indonesia Stock Exchange during 2009 until 2013, there are 35 manufacturing company observations fulfilling the sample criteria. The analysis method used in the research is multiple regression analysis. The result of this research show that (1) investment opportunity set, total asset turn over, and earning per share simultaneously have an effect on the cash dividend, (2) total asset turn over, and earning per share partially have an effect on the cash dividend (3) investment opportunity set have not effect on the cash dividend.